1987
DOI: 10.1159/000199495
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A Status in 137 Patients with Crohn’s Disease

Abstract: Serum retinol and serum carotene concentrations were determined over a 6-month period in 137 outpatients with Crohn’s disease. Serum retinol measurements were within the reference range for all patients at each assessment period, while serum carotene levels were low in about one quarter of the patients. Of the 56 patients who completed 48-hour stool collections, 41 % had stool fat values exceeding the reference value. Serum retinol concentrations were not significantly correlated with the serum carotene concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Several studies have evaluated the deficiency of serum VA levels and disease activity in IBD patients. However, there were contradictory results with some studies showing correlation and some showing no association with disease activity in patients with IBD. Our study, however, supports that low VA levels could be associated with exacerbation of the disease in UC patients.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have evaluated the deficiency of serum VA levels and disease activity in IBD patients. However, there were contradictory results with some studies showing correlation and some showing no association with disease activity in patients with IBD. Our study, however, supports that low VA levels could be associated with exacerbation of the disease in UC patients.…”
Section: Discussionmentioning
confidence: 98%
“…Patients with IBD are at risk of developing fat‐soluble vitamin deficiency because of low nutrient intake, steatorrhea, or gastrointestinal losses during disease flares. Studies have found low serum vitamin A and E levels in a subset of adults and children and young adults with IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Though Crohn's disease could in theory contribute to malabsorption, in a study of 137 patients with Crohn's disease retinol levels were found to be normal. 10 In patient 2, cirrhosis may have exacerbated an underlying deficiency by reducing hepatic stores and the production of retinol binding protein. A study of fat soluble vitamin deficiency in bariatric surgery patients demonstrated that vitamin A deficiency progressively worsens as long as 4 years postoperatively despite vitamin supplementation.…”
Section: Discussionmentioning
confidence: 99%